2013
DOI: 10.1155/2013/718049
|View full text |Cite
|
Sign up to set email alerts
|

Potential Roles ofStevia rebaudianaBertoni in Abrogating Insulin Resistance and Diabetes: A Review

Abstract: Insulin resistance is a key factor in metabolic disorders like hyperglycemia and hyperinsulinemia, which are promoted by obesity and may later lead to Type II diabetes mellitus. In recent years, researchers have identified links between insulin resistance and many noncommunicable illnesses other than diabetes. Hence, studying insulin resistance is of particular importance in unravelling the pathways employed by such diseases. In this review, mechanisms involving free fatty acids, adipocytokines such as TNFα an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 54 publications
1
19
0
1
Order By: Relevance
“…Previous studies have shown correlations between ghrelin to both BMI and insulin, However, they did not recommend its routine use of such parameters [11,12]. We have observed higher IR and insulin in T2DM with obesity similar to previously documented [13,14].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Previous studies have shown correlations between ghrelin to both BMI and insulin, However, they did not recommend its routine use of such parameters [11,12]. We have observed higher IR and insulin in T2DM with obesity similar to previously documented [13,14].…”
Section: Discussionsupporting
confidence: 79%
“…IR is a key factor in metabolic disorders such as hyperglycemia and hyperinsulinemia, which are promoted by obesity and may later lead to T2DM. Systematic assessment of barriers of insulin therapy, individualized diabetes treatment plans and information of patients may help to overcome such negative attitudes, leading to quicker initiation of therapy, improved adherence to treatment, and a better quality of life [13,14].…”
Section: Homa-β and Dmmentioning
confidence: 99%
“…The role of IL-6 level in insulin resistance, occurrence of type II diabetes, and consequent complications (eg, retinopathy and endothelial cell dysfunction) has been confirmed in the literature (13). Therefore, it seems that IL-6 level is a therapeutic target for overcoming the insulin resistance phenomenon (14).…”
Section: Introductionmentioning
confidence: 88%
“…These chemical agents can eventually increase vascular function and reduce impaired lipid and glucose metabolism, as well as inflammation (13,14). Nevertheless, lactic acidosis, for instance, is the most serious complication of biguanides (15).…”
Section: Introductionmentioning
confidence: 99%
“…They also showed increase in the level of GPx suggesting its antioxidant effects. [75]. Stevioside transport is very low but steviol by passive diffusion and carrier-mediated transport is much faster.…”
Section: Anti-diabeticmentioning
confidence: 99%